Bitter Flavored, Soft Composites for Wearables Designed to Reduce Risks of Choking in Infants. Issue 39 (8th August 2021) - Cho, Donghwi; Li, Rui; Jeong, Hyoyoung; Li, Shupeng; Wu, Changsheng; Tzavelis, Andreas; Yoo, Seonggwang; Kwak, Sung Soo; Huang, Yonggang; Rogers, John A.
Abstract: Wireless, skin‐integrated devices for continuous, clinical‐quality monitoring of vital signs have the potential to greatly improve the care of patients in neonatal and pediatric intensive‐care units. These same technologies can also be used in the home, across a broad spectrum of ages, from beginning to end of life. Although miniaturized forms of such devices minimize patient burden and improve compliance, they represent life‐threatening choking hazards for infants. A materials strategy is presented here to address this concern. Specifically, composite materials are introduced as soft encapsulating layers and gentle adhesives that release chemical compounds designed to elicit an intense bitter taste when placed in the mouth. Reflexive reactions to this sensation strongly reduce the potential for ingestion, as a safety feature. The materials systems described involve a non‐toxic bitterant (denatonium benzoate) as a dopant in an elastomeric (poly(dimethylsiloxane)) or hydrogel matrix. Experimental and computational studies of these composite materials and the kinetics of release of the bitterant define the key properties. Incorporation into various wireless skin‐integrated sensors demonstrates their utility in functional systems. This simple strategy offers valuable protective capabilities, with broad practical relevance to the welfare of children monitored with wearable devices. Abstract : Bitter‐flavored formulations in soft encapsulating layers and hydrogel adhesives for skin‐interfaced wireless devices reduce risks of choking with infants. A bitter dopant, denatonium benzoate, integrated into soft silicone elastomers and hydrogels triggers a reflexive response when dissolved in saliva. Demonstrations in a variety of devices for physiological monitoring highlight the compatibility of these unusual composite materials in clinical‐grade wearables.